Follow-up services for delirium after COVID-19—where now?. (22nd January 2021) - Rahman, Shibley; Byatt, Kit
Abstract: Delirium is a common presentation in older inpatients with coronavirus disease 2019 (COVID-19), and a risk factor for cognitive decline at discharge. The glaring gaps in the service provision in delirium care, regardless of aetiology, after a hospital admission pre-existed the pandemic, but the pandemic arguably offers an opportunity now to address them. Whilst a delirium episode in itself is not a long-term condition, the context of it may well be, and therefore patients might benefit from personalised care and support planning. There is no reason to believe that the delirium following COVID-19 is fundamentally different from any other delirium. We propose that the needs of older patients who have experienced delirium including from COVID-19 could be addressed through a new model of post-acute delirium care that combines early supported discharge, including discharge-to-assess, with community-based follow-up to assess for persistent delirium and early new long-term cognitive impairment. Such a drive could be structurally integrated with existing memory clinic services. To succeed, such an ambition has to be flexible, adaptable and person-centred. To understand the impact on resource and service utilisation, techniques of quality improvement should be implemented, and appropriate metrics reflecting both process and outcome will be essential to underpin robust and sustainable business cases to support implementation of delirium care as a long-term solution.